The Effectiveness of Endorphin Massage Combined with Nutmeg (Myristica fragrans) Aromatherapy in Reducing Pain and Anxiety During the Active Phase of the First Stage of Labor at Labuha Regional Hospital - Warda, Warda; Kristiarini, Juda Julia; Suryantara, Bima (Griya Eka Sejahtera, 2025)
Background: Labor pain and anxiety, primarily caused by uterine contractions, are common experiences during childbirth and can lead to complications if not properly managed. Non-pharmacological methods such as endorphin massage and nutmeg aromatherapy offer promising alternatives for pain and anxiety reduction. This study aimed to evaluate the effectiveness of endorphin massage in combination with nutmeg aromatherapy in reducing pain and anxiety during the active phase of the first stage of labor.Methods: A quasi-experimental design with a pretest-posttest control group was employed. The intervention group received endorphin massage alongside nutmeg aromatherapy, while the control group was given nutmeg aromatherapy alone. A total of 52 laboring women in the active phase of first-stage labor at Labuha Regional Hospital during May–June 2025 were recruited using purposive sampling, with 26 participants in each group. Data were collected using questionnaires and observation sheets. Descriptive statistics, the Kolmogorov-Smirnov normality test, and both paired and unpaired statistical tests were utilized. The Mann-Whitney U test was used to assess group differences.Results: In the control group, Wilcoxon tests showed significant reductions in both pain (p = 0.000) and anxiety levels (p = 0.000) following the aromatherapy intervention. The treatment group demonstrated a significantly greater reduction in pain (Z = -6.102, p = 0.000) and anxiety (Z = -3.074, p = 0.002) compared to the control group, indicating the added benefit of endorphin massage.Conclusion: The combination of endorphin massage and nutmeg aromatherapy is effective in significantly reducing labor-related pain and anxiety. This method may be recommended as a supportive non-pharmacological intervention to enhance maternal comfort and care quality during labor, particularly by midwives.